(untitled) (Italiano LinguaDue, 2025)
This article explores differences in the realisation of one apology strategy between Australian learners of Italian, native speakers of Italian and native speakers of Australian English. The strategy in question is providing an explanation, which is here investigated through an analysis of elicited emails addressed to academic staff at university. The analysis demonstrates that while Australian learners of Italian tend to resort to this strategy as an obligatory stage in the performance of apologies, native Italian speakers frequently omit it. Such difference between the two groups is further explored through interview data and fieldnotes which present participants’ perceptions of providing an explanation, which yield insights into the rationale underlying such choices of constructing and/or omitting explanations in order to account for offences. The findings from all analyses evidence the highly contextualised nature of the speech act of apology, highlighting the Australian and Italian students’ diverse understandings of the different institutional roles of professors and tutors in their respective cultural and institutional contexts. Il ruolo della spiegazione nello scusarsi tramite le mail: un’approccio cross-culturale Questo articolo esplora le differenze nella realizzazione della strategia di scusarsi fra tre gruppi: gli apprendenti l’taliano LS australiani, parlanti nativi di italiano ed i parlanti nativi dell’inglese australiano. Specificamente, la strategia in questione è fornire una spiegazione, la quale è studiata attraverso un’analisi delle mail indirizzate agli staff accademici all’università. L’analisi dimostra che, mentre gli apprendenti australiani tendono di usare questa strategia come una fase obbligatoria nella formazione delle scuse, spesso i parlanti nativi dell’italiano l’omettono. Questa differenza tra i due gruppi viene esplorata ulteriormente con dati tratti dalle interviste e dai fieldnotes che presentono le percezioni dei partecipanti riguardo il fornire una spiegazione. Queste percezioni offrono approfondimenti riguardo alla logica sottostante la scelta di costruire e/o omettere le spiegazioni per le offese. I risultati delle analisi evidenziano la natura altamente contestualizzata dell’atto di scusarsi, mettendo in luce le diverse comprensioni degli studenti australiani e degli studenti italiani circa i ruoli istituzionali dei professori e dei tutor nei relativi contesti culturali e istituzionali.